Early activating somatic PIK3CA mutations promote ectopic muscle development and upper limb overgrowth. Issue 2 (9th May 2019) - Frisk, Sofia; Taylan, Fulya; Blaszczyk, Izabela; Nennesmo, Inger; Annerén, Göran; Herm, Bettina; Stattin, Eva‐Lena; Zachariadis, Vasilios; Lindstrand, Anna; Tesi, Bianca; Laurell, Tobias; Nordgren, Ann
Abstract: PIK3CA ‐related overgrowth spectrum is a group of rare genetic disorders with asymmetric overgrowth caused by somatic mosaic PIK3CA mutations. Here, we report clinical data and molecular findings from two patients with congenital muscular upper limb overgrowth and aberrant anatomy. During debulking surgery, numerous ectopic muscles were found in the upper limbs of the patients. DNA sequencing, followed by digital polymerase chain reaction, was performed on DNA extracted from biopsies from hypertrophic ectopic muscles and identified the somatic mosaic PIK3CA hotspot mutations c.3140A > G, p.(His1047Arg) and c.1624G > A, p.(Glu542Lys) in a male (patient 1) and a female (patient 2) patient, respectively. Patient 1 had four ectopic muscles and unilateral isolated muscular overgrowth while patient 2 had 13 ectopic muscles and bilateral isolated muscular overgrowth of both upper limbs, indicating that her mutation occurred at early pre‐somitic mesoderm state. The finding of PIK3CA mutations in ectopic muscles highlights the importance of PIK3CA in cell fate in early human embryonic development. Moreover, our findings provide evidence that the disease phenotype depends on the timing of PIK3CA mutagenesis during embryogenesis and confirm the diagnostic entity PIK3CA ‐related muscular overgrowth with ectopic accessory muscles. Abstract :